Study of the coding system by doctors and nurses for the diagnosis of patient diseases in hospitals - Sudirahayu, Ika; Mira ZAMIDA (RADINKA JAYA UTAMA PUBLISHER, 2024)
Coding is one of the data processing activities to produce health information, namely by coding disease diagnoses based on ICD-10. The purpose of this study was to get an overview of the coding process by doctors and nurses for the patient's disease diagnosis and the suitability of the coding results at Panembang Senopati Hospital. A descriptive case study using a cross-sectional approach. The population in this study were officers and stakeholders as well as medical record documents for outpatient polyclinic patients, consisting of 9 doctor respondents, 10 nurse respondents, 1 respondent head of medical records, and 1 medical committee chairman. The sampling technique used is purposive sampling. The results of the study found that the coding process was carried out by doctors and nurses at Panemban Senopati Hospital, beginning with an appeal from the medical committee, which was issued with the consideration that the doctor knew more about the diagnosis made, the doctor disposed of it to the nurse if he did not have time to code. Doctors and nurses code using snippets. The diagnosis was coded by a doctor under the complete ICD-10 by 87%, while those that did not match were 13%. Diagnosis coded by nurses according to ICD-10 and completed by 82%, while those that are not appropriate are 18%. The diagnosis of entries by reporting officers according to ICD-10 and complete was 85.5%, while those who were not under ICD-10 were 14.5%.